1998
DOI: 10.1159/000010024
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and Membrane Ca<sup>2+</sup> and Mg<sup>2+</sup> Concentrations in Normal Pregnancy and in Preeclampsia

Abstract: Objective: Changes in intracellular Ca2+ and Mg2+ concentrations seem to be involved in the pathogenesis of preeclampsia, whereas the role of cell membranes has not been studied in detail yet. To investigate the changes in Ca2+ and Mg2+ metabolism in normal pregnancy and preeclampsia, plasma and membrane Ca2+ and Mg2+ concentrations were determined in a clinical study as compared to healthy subjects. Study Design: 25 healthy female subjects, 22 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 33 publications
1
3
0
1
Order By: Relevance
“…This supports an association between altered calcium metabolism and pre-eclampsia. Our findings in the present study are in concurrence with the observations of Kumru et al [14], Joshi et al [34], Sukonpan and Phunpong [35], Kisters et al [39], and Kosch et al [40], although an opposite trend has also been reported [41,42]. Somehow, serum levels of calcium seem to play a part in the development of pre-eclampsia, as it has been seen that a reduction in serum calcium level causes increase in release of parathyroid hormone and renin, which in turn cause increase in intracellular calcium in vascular smooth muscle.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This supports an association between altered calcium metabolism and pre-eclampsia. Our findings in the present study are in concurrence with the observations of Kumru et al [14], Joshi et al [34], Sukonpan and Phunpong [35], Kisters et al [39], and Kosch et al [40], although an opposite trend has also been reported [41,42]. Somehow, serum levels of calcium seem to play a part in the development of pre-eclampsia, as it has been seen that a reduction in serum calcium level causes increase in release of parathyroid hormone and renin, which in turn cause increase in intracellular calcium in vascular smooth muscle.…”
Section: Discussionsupporting
confidence: 94%
“…However, the data from these studies are not so equivocal. No alteration [2,14,37], elevation [43,44], or reduction [33][34][35]39] in plasma or serum magnesium concentration have been demonstrated in pre-eclamptic women. Similarly, no change [37,45], elevation [46,47], or decrease [14,34,48,49] in serum or plasma zinc has been reported in pre-eclamptic women as compared to normal pregnant controls.…”
Section: Discussionmentioning
confidence: 99%
“…Red blood cell ghosts were prepared with a modification of a previously described method [25]. Aliquots of BM and MVM were washed three times by centrifugation-resuspension at 47,500 ×g for 45 min.…”
Section: Methodsmentioning
confidence: 99%
“…It is important to note although estrogen is known to increase TRPM6 expression, plasma estrogen and magnesium levels are inversely related both in women of reproductive age [ 40 ] and in menopausal women[ 41 ]. Interestingly, while some studies have reported lower plasma magnesium levels in pregnancy [ 42 ], a recent longitudinal study in pregnant women reported that serum magnesium levels were similar in all three trimesters, despite the large increase in plasma estrogen that occurs in the third trimester [ 43 ]. This suggests that there are additional mechanisms contributing to the regulation of TRPM6 and magnesium homeostasis during pregnancy to maintain physiologically normal levels of magnesium despite the large hormonal changes that occur in pregnancy.…”
Section: Discussionmentioning
confidence: 99%